2011
DOI: 10.1002/bit.23246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nanoparticle‐immobilized cellulase for improved ethanol yield in simultaneous saccharification and fermentation reactions

Abstract: Ethanol yields were 2.1 (P = 0.06) to 2.3 (P = 0.01) times higher in simultaneous saccharification and fermentation (SSF) reactions of microcrystalline cellulose when cellulase was physisorbed on silica nanoparticles compared to enzyme in solution. In SSF reactions, cellulose is hydrolyzed to glucose by cellulase while yeast simultaneously ferments glucose to ethanol. The 35°C temperature and the presence of ethanol in SSF reactions are not optimal conditions for cellulase. Immobilization onto solid supports c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…Furthermore, the addition of Mn 2+ both initiated the anaerobic fermentation reaction at a lower temperature and decreased the cellulase dosage from 20 U/g to 10 U/g. Due to the reduced cellulose dosage and the reduced energy consumption allowed by the initiation of the anaerobic fermentation reaction at lower temperature (Yanase et al 2010;Lupoi and Smith 2011), ethanol production costs in the group with the addition of Mn 2+ were reduced. Table 3 shows that the hemicellulose content of cornstalks increased from 32.7% to 54.9%.…”
Section: Process Optimization Of Ethanol Production From Cornstalksmentioning
confidence: 99%
“…Furthermore, the addition of Mn 2+ both initiated the anaerobic fermentation reaction at a lower temperature and decreased the cellulase dosage from 20 U/g to 10 U/g. Due to the reduced cellulose dosage and the reduced energy consumption allowed by the initiation of the anaerobic fermentation reaction at lower temperature (Yanase et al 2010;Lupoi and Smith 2011), ethanol production costs in the group with the addition of Mn 2+ were reduced. Table 3 shows that the hemicellulose content of cornstalks increased from 32.7% to 54.9%.…”
Section: Process Optimization Of Ethanol Production From Cornstalksmentioning
confidence: 99%
“…Also, SHF has a faster hydrolysis rate than does SSF under optimized conditions [11,39]. In SSF process, cellulose is hydrolyzed to glucose by cellulase, while yeast spontaneously ferments glucose to ethanol [54]. The SSF usually has a higher productivity (ethanol produced per unit mass of dried feedstock per unit time, g/g.h) than does SHF, since SSF has a shorter operating time [39].…”
Section: Process Alternativesmentioning
confidence: 99%
“…SSF). In one study, dissolved cellulase (500 µl, in 10 mM acetate buffer, pH 4.8 with 0.01 % (w/v) sodium azide) was immobilized on Aerosol OX-50 silica (40 nm average diameter particle, 1.4 m 2 surface area), and the SSF was carried out using this coated silica [54]. The results showed that the ethanol yields of the SSF process containing immobilized enzyme were 2.3 and 2.1 times higher than that of the SSF process containing enzyme in solutions at pH 4.8 and 5.3, respectively.…”
Section: Process Alternativesmentioning
confidence: 99%
See 2 more Smart Citations